Method of node distribution for heterogeneous WMSN based on load balancing - Yong-hong ZHU; En-jie DING (Tongxin xuebao)
Multiple hop transmission in wireless sensor networks(WSN)would bring the energy hole problem near the sink.It proved that the energy hole problem would appear in any position in heterogeneous wireless multimedia sensor networks and propose a method of the node distribution based on load balancing to solve the problem.The energy consumption was analyzed on the basis of considering the data compression ratio and the energy consumed for data transmission and processing.It proved that in heterogeneous WMSN the energy consumption of data processing would affect the node distribution and define a word that profit of data processing.The simulation results show that the energy utilization rate and the survival time of the network can be effectively improved by using the method proposed.